OPTIMIZATION OF POTATO FLOUR FOR DEVELOPMENT OF BISCUITS BY USING RESPONSE SURFACE METHODOLOGY - Giri, Namrata Ankush; Mridula, D (Potato Journal, 2017)
The present study was concerned with to optimize the formulation of potato flour for development of biscuits using a central composite design of Response Surface Methodology. The variables considered for the study were potato flour (20-50%) and refined wheat flour (50-80%) while the responses were spread ratio, sensory texture and overall acceptability. Potato flour and refined wheat flour both significantly affected (p